FRI0485 RISK OF PROGRESSION OF IDIOPATHIC PULMONARY FIBROSIS TO CONNECTIVE TISSUE DISEASE. (2nd June 2020) - Ghang, B.; Nam, S. H.; Kim, Y. G.; Yoo, B.; Lee, C. K.
Abstract : Background: Connective tissue disease (CTD) may be observed during the course of idiopathic pulmonary fibrosis (IPF). However, clinical factors associated with the development of CTD in patients with IPF have not yet been identified. These factors might be valuable clues for determining the pathogenesis of pulmonary fibrosis in patients with CTD. We hypothesize that some IPF patients have a clinically significant association with autoimmunity, and that autoantibodies are important biomarkers for identifying these patients. Objectives: Based on this hypothesis, we investigated whether the serology criteria (anti-neutrophil cytoplasmic antibody (ANCA) or autoantibodies that met the serology criteria for interstitial pneumonitis with autoimmune features (IPAF)) were associated with the development of CTD during the clinical course of IPF in the patients from our previous study(1), with a particular focus on which antibodies have a significant association with the development of CTD. Methods: We retrospectively reviewed the records of 527 patients with a first diagnosis of IPF between January 2007 and March 2014, and investigated the length of time from first visit to the clinic for IPF diagnosis (baseline) to CTD diagnosis by an expert rheumatologist in patients with IPF. Multivariable Cox proportional-hazards models with backward elimination were used to investigate the risk factors for the development of CTD. Results: CTD developed in 15 patients at a median of 2.1 years (range 1.2 to 4.8) after IPF diagnosis. All these patients had ANCA or autoantibodies that met the serology criteria for IPAF. A significant number of IPF patients with high titers of RF, ACPA or MPO-ANCA tested at first visit to the clinic progressed to CTD(Figure 1 ). Survival duration for IPF patients with progression to CTD was 5.3 [3.8; 6.7] years, which was significantly longer than for the IPF patients without progression to CTD (2.9 [1.7; 4.8], p = 0.001). Independent risk factors for development of CTD in IPF patients included female gender (adjusted hazard ratio (HR) 5.319, p = 0.0082), titer of rheumatoid factor (RF) (adjusted HR 1.006, p = 0.022), titer of anti-citrullinated protein antibody (ACPA) (adjusted HR 1.009, p = 0.0011), and titer of myeloperoxidase (MPO) ANCA (adjusted HR 1.02, p < 0.0001). Conclusion: We observed development of CTD in IPF patients with ANCA or autoantibodies that met the IPAF serology criteria. Among these autoantibodies, RF, ACPA, and MPO-ANCA were significantly associated with the development of CTD in IPF patients. Progression to CTD is uncommon in IPF patients, but a significant number of IPF patients with high titers of RF, ACPA or MPO-ANCA progressed to connective tissue disease. IPF with high titers of RF, ACPA or MPO-ANCA might be the initial clinical manifestation of connective tissue disease. Further studies are needed to investigate the role of RF, ACPA, and MPO-ANCA in development of pulmonary fibrosis. References: [1]Ghang B, Lee J, Chan Kwon O, Ahn SM, Oh JS, Hong S, et al. Clinical significance of autoantibody positivity in idiopathic pulmonary fibrosis. Respir Med. 2019;155:43-8. Disclosure of Interests: None declared